Do Gender Disparities Exist Despite a Negative Gender Earnings Gap? - CARABALLO-CUETO, JOSÉ; SEGARRA-ALMÉSTICA, EILEEN (Economía)
In 2009, for the first time, Puerto Rico's unconditional median earnings gender gap presented a statistically significant negative sign. We document the elements that lead to an overall improvement in women's economic position and find that the unconditional earnings gap turns positive once observable characteristics are considered. For instance, we find that the negative gender gap disappears when we adjust for educational attainments as a new indicator of gender gaps. In general, relative differences in returns on education and a glass ceiling effect moderated by dependent children are two of the explanatory factors allowing for the continuation of gender disparities within groups. There is also a direct association between women's representation in a given occupation/education group and the gender earnings gap.